Student Response to the Implementation of E-Module-Assisted Cybergogy in Junior High School Students - Ramadhani, Novitasari; Subekti, Hasan (Jurnal Pijar Mipa, 2025)
The low involvement of students in learning is still a challenge, one of which is influenced by the lecture method, which is still dominant in the teaching and learning process. The application of technology-based learning, such as e-module-assisted cybergoth, is expected to increase students' positive responses. This study aims to analyze students' responses to the application of e-module-assisted cybergogy in science learning. This study uses a quasi-experimental method with a one-shot case study design involving 32-grade VIII-D SMPN 1 Bagor students. Data was collected through student response questionnaires and analyzed using descriptive statistics. The results showed that implementing e-module-assisted cybergogy resulted in very positive student responses, with an average response score of 99.1%. In conclusion, this approach can increase student engagement in science learning. This research implies that educators can adopt e-module-assisted cybergogy to create more interactive and innovative learning.